2022
DOI: 10.1021/acsaelm.2c01076
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Organic and Inorganic Hole and Electron Transport Layers for Organic Solar Cells: Basic Concept and Device Performance

Abstract: The emergence of nonfullerene small-molecule acceptors (NFSMA) with the advantages of synthetic versatility, high absorption coefficient in wide wavelength range, and high thermal stability has attained the power conversion efficiency (PCE) exceeding 19% for resulted organic solar cells (OSCs) with the optimization of interface engineering and active layer morphology. Interfacial layers including both hole transporting layer (HTL) and electron transporting layer (ETL) are equally important in the OSCs for faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 263 publications
0
22
0
Order By: Relevance
“…[58] Later, it is shown that due to the development of the new non-fullerene acceptor (NFA) and D-A conjugate polymer, device engineering, and improvement in the surface morphology, the efficiency of the BHJ OSCs has accomplished significant evolution with an efficiency more than 19%. [37,[59][60][61][62][63][64][65][66][67] However, to realize the high PCE compared to other competitive technologies, enhancing the light-harvesting ability of the active layer is the prerequisite issue. Though, it is difficult to cover the full solar spectrum with a BHJ consisting of one donor and one acceptor due to the intrinsic light absorption properties of organic materials, which also imposes a limitation on the PCE improvement.…”
Section: Osc Developmentmentioning
confidence: 99%
“…[58] Later, it is shown that due to the development of the new non-fullerene acceptor (NFA) and D-A conjugate polymer, device engineering, and improvement in the surface morphology, the efficiency of the BHJ OSCs has accomplished significant evolution with an efficiency more than 19%. [37,[59][60][61][62][63][64][65][66][67] However, to realize the high PCE compared to other competitive technologies, enhancing the light-harvesting ability of the active layer is the prerequisite issue. Though, it is difficult to cover the full solar spectrum with a BHJ consisting of one donor and one acceptor due to the intrinsic light absorption properties of organic materials, which also imposes a limitation on the PCE improvement.…”
Section: Osc Developmentmentioning
confidence: 99%
“…Over the last few years, organic solar cells (OSCs) have emerged as one of the promising third generation photovoltaic technologies due to the unprecedented improvement in their device performance. Owing to its unique advantages like low production cost, roll-to-roll solution processability, lightweight, and mechanical flexibility, this technology has potential in the eco-friendly photovoltaic market, especially in building integrated photovoltaics. ,, A certain threshold in power conversion efficiency (PCE), device stability, and production cost needs to be achieved for future commercialization of OSCs. At present, the PCE has been improved more than 19% in single-junction solar cells, which is largely driven by the state-of-the-art research in developing nonfullerene acceptor (NFA) materials, device optimization, and understanding the working mechanism. ,, Although a high PCE has been often reported, their open circuit voltage ( V OC ) lags behind that of inorganic counterparts, indicating that V OC loss (Δ V OC ) in OSCs is still substantial. The charge transfer (CT) state at the donor–acceptor interface and the different recombination processes of charge carriers are the main contributing factors to Δ V OC . Until recently, it was recognized that the energy level offset between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) of at least 0.3 eV is necessary to obtain a fast and efficient charge generation at the donor–acceptor (D/A) interface. This energy level offset generally limits the further improvement in the performance of fullerene-based OSCs. , However, with a rapid development in NFAs and conjugate polymers, previous studies have shown that efficient free charge generation can be maintained even at a lower HOMO energy offset (Δ E HOMO ) below 0.2 eV. ,,, Many studies on voltage loss based on the Shockley–Queisser (SQ) theory have demonstrated that the V OC loss in NFA-based devices can be reduced near to 0.4 V without losing the high external quantum efficiency (EQE) if the energy level offset decreases below 0.2 eV. ,,,…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous attempts in the development of organic solar cells (OSCs) such as synthesis of novel organic semiconducting materials, controlling the photoactive layer morphology, nano-engineering at the interfaces, understanding the detailed photo-physics of devices, etc., their power conversion efficiency (PCE) remains below the Shockley–Queisser limit. The major hurdle in improving the performance of OSCs is overcoming the issues related to the fundamental tradeoff between ray optic path length and Augur charge-carrier recombination losses. Due to the lower charge-carrier mobility of organic semiconductors, the physical thickness of photoactive layers is needed to maintain as low as possible to minimize the recombination losses, which certainly limits light absorption. To overcome this issue, researchers have designed an optically thick medium by employing the elevated local density of optical states (LDOS) in physically thin photoactive layers, using many innovative strategies such as diffraction gratings, V-shaped light trapping structures, photonic crystals, and metal nanostructures. , Among these methods, incorporating the plasmonic metal nanostructures is a simple and effective way to attain higher LDOS, which can provide absorption enhancement factors several times higher than the Yablonovitch limit. , Upon interaction with incident light, the metal nanostructures induce two radiative plasmonic effects, near-field enhancement, and far-field scattering, which considerably increase the electric field intensity and optical path length inside the active layer, respectively. , These effects crucially depend on the size and the location of metal nanostructures in the devices.…”
Section: Introductionmentioning
confidence: 99%